“The mill whistle was blowing and the Germans were coming”: Industrial Soundscapes, World War II, and Remembrance in Corner Brook, Newfoundland - Tulk, Janice (Ethnologies, 2012)
In summer 2007, while conducting maintenance on the mill’s structure, the Corner Brook Pulp and Paper Mill silenced the whistle that had been part of the local “soundscape” (Schafer 1977) for more than eighty years. When the whistle did not return immediately, public outcry was voiced in the local newspaper over the loss of part of the city’s heritage. Its return in December 2007 at half the previous daily frequency provided the impetus for a collection project.While the mill whistle is an important tool that marks the passage of time, regulates the movement of bodies, and signals trouble at the mill (such as a fire), its significance to the community extends beyond the utilitarian. It plays a role in memorialization (sounding on Remembrance Day) and celebration (marking, for example, the end of WWII), and has become a familiar icon for local song-writers and authors alike. This article provides an overview of “The Mill Whistle Project” designed to document the mill whistle in Corner Brook, describes the historic functions of the mill whistle, and identifies alternative uses of the whistle over time. It then interrogates the whistle’s relationship to World War II and Remembrance Day, demonstrating its extension as a community-wide notification system, its mobilization as a means of celebration, and its continuing role in memorialisation.